(untitled) (Raparin Journal of Humanities (RJH), 2024)
Qalachwalan basin is important agricultural and it is one of the main water resources for Slemani city. The basin contains useful natural resources that are conducive to agricultural development. As the area is a hill country, Gavrilovic model was chosen to get the size and amount of water erosion to determine the erosion risks that the basin is facing. This research was conducted based on Gavrilovic (EPM) model using (RS & GIS) to determine the level, amount, and size of water erosion of Qalachwalan basin. We found out that, through the research, the slopes that are in the direction of the estuaries face water erosion much more due to the form of the basin in its creation, which has many slopes and little vegetation on the cliffs that are a main cause of the speedy runoff. Also, poor planning to confront or reduce the risks of flood which increases the erosions. The erosion estimated based on Gavrilovic model between very weak erosion at less than (100 m3/km2/year) and very strong erosion at (5000 – 20000 m3/km2/year). The basin generally lies in the circle of moderate water erosion at (1230 m3/km2/year). Therefore, for the secondary basins (e.g. Jogasur, Mawakan, and estuary) the erosion based on Gavrilovic model was high consecutively in this way (1720, 2584 and 4356 m3/km2/year). Our results very impotent for local government stockholders to establishment new dams in cliffs areas for agriculture and determine life cycle of these dams in this areas, and find new solution to reduce soil erosions in near future.